CD71+ Erythroid Cells in Human Neonates Exhibit Immunosuppressive Properties and Compromise Immune Response Against Systemic Infection in Neonatal Mice - Elahi, Shokrollah; Vega-López, Marco Antonio; Herman-Miguel, Vladimir; Ramírez-Estudillo, Carmen; Mancilla-Ramírez, Javier; Motyka, Bruce; West, Lori; Oyegbami, Olaide (Frontiers in Immunology, 2020)
Newborns are highly susceptible to infectious diseases. The underlying mechanism of neonatal infection susceptibility has generally been related to their under-developed immune system. Nevertheless, this notion has recently been challenged by the discovery of the physiological abundance of immunosuppressive erythroid precursors CD71+erythroid cells (CECs) in newborn mice and human cord blood. Here, as proof of concept, we show that these cells are also abundant in the peripheral blood of human newborns. Although their frequency appears to be more variable compared to their counterparts in mice, they rapidly decline by 4 weeks of age. However, their proportion remains significantly higher in infants up to six months of age compared to older infants. We found CD45 expressing CECs, as erythroid progenitors, were the prominent source of reactive oxygen species (ROS) production in both humans and mice. Interestingly, a higher proportion of CD45+CECs was observed in the spleen versus bone marrow of neonatal mice, which was associated with a higher ROS production by splenic CECs compared to their siblings in the bone marrow. CECs from human newborns suppressed cytokine production by CD14 monocytes and T cells, which was partially abrogated by apocynin in vitro. Moreover, the depletion of CECs in neonatal mice increased the number of activated effector immune cells in their spleen and liver, which rendered them more resistant to Listeria monocytogenes infection. This was evident by a significant reduction in the bacteria load in the spleen, liver and brain of treated-mice compared to the control group, which enhanced their survival rate. Our finding highlights the immunoregulatory processes mediated by CECs in newborns. Thus, such tightly regulated immune system in newborns/infants may explain one potential mechanism for the asymptomatic or mild COVID-19 infection in this population.